Trato social a sobrevivientes de campos de concentración alemanes en la Europa de postguerra y el síndrome de KZ. - U., Horacio Riquelme (Cuadernos Médico Sociales, 2021)
This article focuses on extreme experiences of prisoners in German concentration camps [KZ] and their psychosocial effects based on the central questions: 1.- Are they accessible to the understanding of people from other fields and other times? and How specific is concentration camp syndrome [SCC]? 2.- What have been the social and psychotherapeutic responses to the various forms of onset (early, middle and late) of the syndrome in the various countries? and 3.- What was the social treatment of survivors of German concentration camps in the various countries of post-war Europe? It introduces the micro world of the KZ in its existential conditions, presenting documented experiences in West Germany, France, Hungary, Norway and Poland and carry out a comparative study on the treatment of those affected by the extreme situation of the National Socialist concentration camp. Its cognitive interest is to update the perception of the pathological effects of KZ in the European context and thus help to understand the current situation in other confines including Latin America and to create clinical instruments of approach and public health policies focused on the damage caused by the repressive action by authoritarian governments.